Nurses’ well-being and its relationship with quality of nursing work life at Alsalam and Al Haram Hospitals, Saudi Arabia - Alharbi, Meshal S.; Albughuli, Mohammed B.; Aljohani, Sami S.; Alraddadi, Yahya A.; Alalawi, Najeeb B.; Alawfi, Hani M.; Al Harbi, Sami M.; Alharbi, Rasha H.; Alreshidi, Ohoud A. (Frontiers in Public Health, 2025)
IntroductionNurses’ well-being is a vital factor influencing healthcare quality, patient safety, and workforce sustainability. In Saudi Arabia, nurses in public hospitals often encounter high workloads, emotional stress, and limited managerial support, potentially affecting both their mental health and professional performance.AimsThis study aimed to assess the well-being of nurses working at Alsalam and Al Haram hospitals in Saudi Arabia and to examine its relationship with the Quality of Nursing Work Life (QNWL).MethodsA cross-sectional census study was conducted in 2025 involving 169 registered nurses from the two hospitals. Data were collected using structured interview questionnaires incorporating three validated tools: The Nurse’s Well-Being Assessment Tool (NWAT), the World Health Organization-Five Well-Being Index (WHO-5), and the QNWL Scale. Statistical analysis was performed using SPSS version 25.ResultsNurses reported moderate overall well-being (mean NWAT score: 62.20 ± 2.9), with notably low scores in work-life balance and emotional/mental health. The WHO-5 index indicated low emotional well-being (mean: 12.70 ± 2.2), reflecting significant emotional distress. The QNWL scores were generally poor (mean: 91.02 ± 6.0), particularly in the areas of managerial support and work-life balance. Moderate scores were observed in nurse-physician relationships and professional fulfillment. A significant positive correlation was found between well-being (NWAT and WHO-5) and QNWL scores (p = 0.001), indicating that higher well-being is associated with better quality of work life. Comparisons between hospitals showed that nurses at Alsalam Hospital had higher QNWL and WHO-5 scores but lower NWAT scores than those at Al Haram Hospital, with statistically significant differences (p < 0.05).ConclusionNurses at both hospitals face multiple well-being challenges that negatively impact their quality of work life. Interventions focusing on mental health support, enhanced managerial engagement, and improved work-life balance are essential. These efforts are crucial for advancing workforce well-being and aligning with the healthcare objectives of Saudi Arabia’s Vision 2030.